2018
DOI: 10.1016/j.calphad.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion multiple study of Co-Ni-Ti system at 1073 K

Abstract: Co-Ni-Ti system is a key system for thein several industrial applications. The thermodynamic and kinetic information of this system is crucial for to optimize the alloy design and process design. However, aAlthough there are many literature works on this aspectthe system has been studied largely, there are is still discrepancies onconfusion about the stability of the ternary phase _Ti(Ni0.5Co0.5)3 phase, and only few data on the diffusion information ofin the intermediate compounds as available. In this work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Finally, it should be mentioned that the extent of this ternary phase may be quite large in the quaternary system as a two-phase FCC+τ domain has been experimentally confirmed for the Co52.5Ni35Ti12.5 composition ([Fe] = 0 at.%, Fig. S6) between 800°C and 1100°C [64,66,67]. Calphad predictions suggest two phases for the considered alloy composition: FCC and Ni3Ti.…”
Section: Comparison Between Experimental Results and Calphad Predictionsmentioning
confidence: 62%
See 1 more Smart Citation
“…Finally, it should be mentioned that the extent of this ternary phase may be quite large in the quaternary system as a two-phase FCC+τ domain has been experimentally confirmed for the Co52.5Ni35Ti12.5 composition ([Fe] = 0 at.%, Fig. S6) between 800°C and 1100°C [64,66,67]. Calphad predictions suggest two phases for the considered alloy composition: FCC and Ni3Ti.…”
Section: Comparison Between Experimental Results and Calphad Predictionsmentioning
confidence: 62%
“…The presence of the (Ni0.5Co0.5)3Ti (τ) ternary phase of hexagonal structure with the Co3V prototype is commonly observed in Co-Ni-Ti alloying systems and has been first identified by Van Loo and Bastin in the ternary system at 900°C using diffusion couple technique [62]. It has been evidenced as a stable phase between 800°C and 1100°C in recent studies [63][64][65][66][67]. The ternary phase is present in a narrow compositional region of the Co-Ni-Ti system between Ni3Ti (D024) and Co3Ti sequence and coordination geometry [65].…”
Section: Comparison Between Experimental Results and Calphad Predictionsmentioning
confidence: 97%
“…in D sublayer, ni content is higher than Co, which increase the tendency to form γ'-ni 3 al phase. in addition, Co and ni do not form binary phases [9], so the γ' of γ + γ' sublayer is consist of more ni 3 al but less Co 3 al. Similarly, the addition of ni has the same effect to Co40al, where ni and al react in solution to form γ'-ni 3 al.…”
Section: Elements Partitioningmentioning
confidence: 99%
“…omori et al [7] studied the partitioning behavior of alloying elements in Co-al-W-based quaternary systems and showed that Ta, nb, Ti, V, Mo and W elements are partitioned into γ' phase rather than γ phase, which can improve the thermal stability of γ' phase [8]. Yuan et al [2,9] reported interfacial diffusion of Co-ni-Ti and Co-ni-Fe systems under 1173 K, and calculated the diffusion coefficients at this temperature. However, there are few reports on elements variations in W-free Co-al-X diffusion interface.…”
Section: Introductionmentioning
confidence: 99%
“…A diffusion multiple of Co-Fe-Ni-Ti were constructed in this work. The work results of Ti-Ni-Co system on this diffusion multiple were published as another work [27].…”
Section: Introductionmentioning
confidence: 96%